Resistance in marine cyanobacteria differs against specialist and generalist cyanophages - Zborowsky, Sophia (Proc Natl Acad Sci U S A, 2019)
Long-term coexistence between unicellular cyanobacteria and their lytic viruses (cyanophages) in the oceans is thought to be due to the presence of sensitive cells in which cyanophages reproduce, ultimately killing the cell, while other cyanobacteria survive due to resistance to infection. Here, we investigated resistance in marine cyanobacteria from the genera Synechococcus and Prochlorococcus and compared modes of resistance against specialist and generalist cyanophages belonging to the T7-like and T4-like cyanophage families. Resistance was extracellular in most interactions against specialist cyanophages irrespective of the phage family, preventing entry into the cell. In contrast, resistance was intracellular in practically all interactions against generalist T4-like cyanophages. The stage of intracellular arrest was interaction-specific, halting at various stages of the infection cycle. Incomplete infection cycles proceeded to various degrees of phage genome transcription and translation as well as phage genome replication in numerous interactions. In a particularly intriguing case, intracellular capsid assembly was observed, but the phage genome was not packaged. The cyanobacteria survived the encounter despite late-stage infection and partial genome degradation. We hypothesize that this is tolerated due to genome polyploidy, which we found for certain strains of both Synechococcus and Prochlorococcus. Our findings unveil a heavy cost of promiscuous entry of generalist phages into nonhost cells that is rarely paid by specialist phages and suggests the presence of unknown mechanisms of intracellular resistance in the marine unicellular cyanobacteria. Furthermore, these findings indicate that the range for virus-mediated horizontal gene transfer extends beyond hosts to nonhost cyanobacterial cells.